Infrastructure coverage and the poor : a global perspective - Komives, Kristin (Policy research working paper, 2001)
The poor in most parts of the world may have electricity (especially in urban areas), but they rarely have water, sewer, and telephone services. When they gain access to local services, however, many do decide to connect